(untitled) (Jurnal Riset Veteriner Indonesia (Journal of The Indonesian Veterinary Research), 2023)
The KUB chicken is one of the local chicken families, which is the result of research by Balitbangtan. This study aimed to determine the performance of KUB chickens with P1 feeding treatment (using 100% commercial feed) and P2 treatment (using 100% local feed). This study used 100 KUB chickens aged two weeks and was reared up to 6 weeks. Chicken performance was measured based on feed consumption, body weight, body weight gain, and feed conversion. The data were analyzed descriptively by presenting the mean, standard deviation, coefficient of diversity and statistical analysis using the T-test. The study results on the performance of KUB chickens in treatment P1 obtained feed consumption of 23.68 and P2 23.25, for feed conversion P1 0.24 and P2 0.23 while the weight gain of P1 was 33.76 and P2 was 47.78. This study concludes that local feed ingredients provide performance (feed consumption, body weight gain, and feed conversion not significantly different from commercial feeds. It can be concluded that local feed ingredients can be used as the main feed in KUB chicken feed formulations.